Chromatin dynamics during DNA damage and repair in plants: new roles for old players - Casati, Paula (2021)
The genome of plants is organized into chromatin. The chromatin structure regulates the rates of DNA metabolic processes such as replication, transcription, DNA recombination, and repair. Different aspects of plant growth and development are regulated by changes in chromatin status by the action of chromatin-remodeling activities. Recent data have also shown that many of these chromatin-associated proteins participate in different aspects of the DNA damage response, regulating DNA damage and repair, cell cycle progression, programmed cell death, and entry into the endocycle. In this review, we present different examples of proteins and chromatin-modifying enzymes with roles during DNA damage responses, demonstrating that rapid changes in chromatin structure are essential to maintain genome stability.